Advances in structural vibration control application of magneto-rheological visco-elastomer. Issue 2 (March 2017) - Ying, Zuguang; Ni, Yiqing
Abstract: Magneto-rheological visco-elastomer (MRVE) as a new smart material developed in recent years has several significant advantages over magneto-rheological liquid. The adjustability of structural dynamics to random environmental excitations is required in vibration control. MRVE can supply considerably adjustable damping and stiffness for structures, and the adjustment of dynamic properties is achieved only by applied magnetic fields with changeless structure design. Increasing researches on MRVE dynamic properties, modeling, and vibration control application are presented. Recent advances in MRVE dynamic properties and structural vibration control application including composite structural vibration mitigation under uniform magnetic fields, vibration response characteristics improvement through harmonic parameter distribution, and optimal bounded parametric control design based on the dynamical programming principle are reviewed. Relevant main methods and results introduced are beneficial to understanding and researches on MRVE application and development. Highlights: New advances in structural vibration control using magnetorheological viscoelastomer. Dynamic optimization of periodic MR viscoelastomer sandwich structures. Optimal vibration control of parameter-excited MR viscoelastomer sandwich structures.